Postoperative Stereotactic Body Radiotherapy for Spinal Metastasis and Predictors of Local Control. Issue 5 (11th February 2021) - Blakaj, Dukagjin M; Palmer, Joshua D; Dibs, Khaled; Olausson, Alexander; Bourekas, Eric C; Boulter, Daniel; Ayan, Ahmet S; Cochran, Eric; Marras, William S; Mageswaran, Prasath; Katzir, Miki; Yildiz, Vedat O; et al.
Abstract: BACKGROUND: Spine surgery is indicated for select patients with mechanical instability, pain, and/or malignant epidural spinal cord compression, with or without neurological compromise. Stereotactic body radiotherapy (SBRT) is an option for durable local control (LC) for metastatic spine disease. OBJECTIVE: To determine factors associated with LC and progression-free survival (PFS) for patients receiving postoperative stereotactic spine radiosurgery. METHODS: We analyzed consecutive patients from 2013 to 2019 treated with surgical intervention followed by SBRT. Surgical interventions included laminectomy and vertebrectomy. SBRT included patients treated with 1 to 5 fractions of radiosurgery. We analyzed LC, PFS, overall survival (OS), and toxicity. Univariate and multivariate analyses were performed. RESULTS: A total of 63 patients were treated with a median follow-up of 12.5 mo. Approximately 75% of patients underwent vertebrectomy and 25% underwent laminectomy. One-year cumulative incidence of local failure was 19%. LC was significantly improved for patients receiving radiosurgery ≤40 d from surgery compared to that for patients receiving radiosurgery ≥40 d from surgery, 94% vs 75%, respectively, at 1 yr ( P = .03). Patients who received preoperative embolization had improved LC with 1-yr LC of 88% vs 76% for those who did not receive preoperative embolization ( P = .037). Significant predictors for LC on multivariate analysis were time from surgery to radiosurgery, higher radiotherapy dose, and preoperative embolization. The 1-yr PFS and OS was 56% and 60%, respectively. CONCLUSION: Postoperative radiosurgery has excellent and durable LC for spine metastasis. An important consideration when planning postoperative radiosurgery is minimizing delay from surgery to radiosurgery. Preoperative embolization and higher radiotherapy dose were associated with improved LC warranting further study. Graphical Abstract: